1992
DOI: 10.1679/aohc.55.179
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and Immunocytochemical Studies of Enamel Tufts in Human Permanent Teeth.

Abstract: Summary. Enamel tufts were exposed after decalcification of the enamel matrix and their fine structures and immunocytochemical characteristics were examined. Under the binocular microscope and the scanning electron microscope (SEM), enamel tufts appeared as corrugated ribbon-like structures located on the dentine parallel to the tooth axis. SEM observation disclosed enamel tufts as bundles of well extended tubular structures with cross striations attributable to hypocalcified enamel sheaths. Plate-like structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
4
18
0
Order By: Relevance
“…At the same time, some of the structures found at this interface, such as enamel tufts and spindles are poorly understood. These structures are less mineralized and contain more protein than does the surrounding enamel (Amizuka et al , 1992; Palamara et al , 1989). The mineral crystals associated with these structures are much smaller than enamel crystals and similar to those found in dentin (Amizuka et al , 1992; Palamara et al , 1989), at the same time no collagen has been found in these structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, some of the structures found at this interface, such as enamel tufts and spindles are poorly understood. These structures are less mineralized and contain more protein than does the surrounding enamel (Amizuka et al , 1992; Palamara et al , 1989). The mineral crystals associated with these structures are much smaller than enamel crystals and similar to those found in dentin (Amizuka et al , 1992; Palamara et al , 1989), at the same time no collagen has been found in these structures.…”
Section: Discussionmentioning
confidence: 99%
“…These structures are less mineralized and contain more protein than does the surrounding enamel (Amizuka et al , 1992; Palamara et al , 1989). The mineral crystals associated with these structures are much smaller than enamel crystals and similar to those found in dentin (Amizuka et al , 1992; Palamara et al , 1989), at the same time no collagen has been found in these structures. Our in vitro mineralization experiments and earlier reports (Tartaix et al , 2004) demonstrate that DMP1 controls the size of the crystals.…”
Section: Discussionmentioning
confidence: 99%
“…Although such lamellae were long thought to start at the enamel surface and progress as ‘outside-in' cracks [73], experimental evidence now suggests that instead they grow from inside to outside as extensions of enamel tufts [57,58]. There is a forest of tufts all around the enamel-dentine junction ready to pick this strain energy up [74,75]. These cracks grow slowly, requiring a sharply increasing force to extend [57,58].…”
Section: Macrofracturementioning
confidence: 99%
“…Both components differ in structure and physical properties. However, no significant evidence has been found so far (1,8).…”
mentioning
confidence: 95%